Implementation forEducation Data Management System based on Remote Control (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The research is subject for effective remote education using multimedia, it is necessary to developefficient management techniques of video information. This requires real-time processing of video information which should be managed and retrieved in a compressed forms. The main technology of compressing video is currently MPEG-2. This implies that it is very important to manage and retrieve video compressed in MPEG-2, and then to process the video in real-time for the remote education environment using multimedia. This paper is to develop the management system of video information which is one of the most critical requirements in remote education systems for managing and retrieving MPEG-2 video